2006
DOI: 10.1093/hmg/ddl166
|View full text |Cite
|
Sign up to set email alerts
|

P2RX7, a gene coding for a purinergic ligand-gated ion channel, is associated with major depressive disorder

Abstract: The P2RX7 gene is located within a region on chromosome 12q24.31 that has been identified as a susceptibility locus for affective disorders by linkage and association studies. P2RX7 is a purinergic ATP-binding calcium channel expressed in neurons as well as in microglial cells in various brain regions. We investigated 29 single nucleotide polymorphisms (SNPs) within the P2RX7 gene and adjacent genes in a sample of 1000 German Caucasian patients suffering from recurrent major depressive disorder (MDD). These we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
186
4
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 233 publications
(202 citation statements)
references
References 46 publications
8
186
4
4
Order By: Relevance
“…Data for association between rs2230912 (P2RX7-E13A) and bipolar disorder was published in the first P2RX7 bipolar study 15 and also in a follow-up study on major depression. 16 The minor allele (G) in all three studies was found at an increased frequency in patients with mood disorder. Table 4 shows the results of a combined analysis of data for rs2230912 from Barden et al 15 and Lucae et al 16 combined with the UCL bipolar data for 3586 individuals.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…Data for association between rs2230912 (P2RX7-E13A) and bipolar disorder was published in the first P2RX7 bipolar study 15 and also in a follow-up study on major depression. 16 The minor allele (G) in all three studies was found at an increased frequency in patients with mood disorder. Table 4 shows the results of a combined analysis of data for rs2230912 from Barden et al 15 and Lucae et al 16 combined with the UCL bipolar data for 3586 individuals.…”
Section: Resultsmentioning
confidence: 79%
“…16 The minor allele (G) in all three studies was found at an increased frequency in patients with mood disorder. Table 4 shows the results of a combined analysis of data for rs2230912 from Barden et al 15 and Lucae et al 16 combined with the UCL bipolar data for 3586 individuals. This analysis showed significant allelic association (P = 0.0025) and genotypic association (P = 0.0005).…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Some interesting novel drug targets came up by these strategies (e.g. Lucae et al 2006;McQuilin et al 2008), but overall, the success in using genotype information for identification of valid drug targets is limited so far. The main reason for this disenchantment is that the genotype provides little information about changes in gene activity following a cellular challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Within this putative region lies the purinergic ATPbinding calcium channel gene (P2X7). A non-synonymous coding SNP within P2X7 (Gln460Arg) is associated with MDD risk (Lucae et al, 2006). P2X7 protein is required for IL-1 (interleukin-1) processing and secretion (Ferrari et al, 2006), highlighting the potential role of immune function in depressive behavior.…”
Section: Genetic Predictors Of Depression and Antidepressant Responsementioning
confidence: 99%